Effect of a Single Dose Montelukast Sodium on Methacholine Chloride PC20 - Beth E Davis; Donald W Cockcroft (Canadian Respiratory Journal)
BACKGROUND: It is currently recommended that leukotriene modifiers (receptor antagonists and synthesis inhibitors) be withheld for a minimum of 24 h before direct bronchoprovocation testing, but there is little evidence to support this recommendation.